The Adaptation of Executive Education Programs in Thailand during the COVID-19 Pandemic - Arriyavat, Treesuvit; Pimpa, Nattavud (Journal of Ecohumanism, 2024)
This study explores the factors influencing the management of an executive education (EE) program in Thailand during COVID-19. The pandemic caused significant disruption, necessitating a rapid shift to online learning and curriculum reassessment. This case study focuses on the redesign of a Thai business school’s EE program. Data was collected through semi-structured interviews with participants and program managers. Key preliminary findings highlight the importance of C-level guest speakers, project-based learning, and a balance of practical and theoretical approaches. The study also underscores the value of online networking, strong alumni networks, and using COVID-19-related content as learning tools. The results suggest that business schools should integrate learning theories to foster innovation and adaptability, ensuring dynamic curricula and impactful research to meet the evolving global landscape.